The Level of Sustainability of Serang Village, Blitar Regency Based on the Spiritual Aspects of the Community Sustainability Assessment (CSA) - Gagas Tegar Hardian; Agung Murti Nugroho; Susilo Kusdiwanggo (Green Publisher Indonesia, 2025)
Community Sustainability Assessment (CSA) was developed to help communities evaluate their achievements and chart a course towards increasing sustainability. In CSA, each of which is as important as the others, are the Environmental, Social and Economic aspects of society. The CSA is a comprehensive checklist that anyone can complete to get a basic idea of how sustainable a community is with a score that is effective for promoting understanding and measuring sustainability in society, and applies to any community. Although it requires a good knowledge of the lifestyle, practices and characteristics of the community, it does not require detailed research, calculations and quantification. One village that is interesting to know about its level of sustainability is Serang Village, Blitar. Serang Tourism Village, Panggungrejo District, Blitar Regency, is included as one of 50 tourist villages where, according to the measurement results, Serang Village has the highest score in terms of the Spiritual Aspect of its community.